Antioxidant, analgetic, and anti-inflammatory activity test of purple leaf ethanol extract (Graptophyllum pictum L. Griff) in vitro and in vivo - Sisca Ocvinta; Niluh Puspita Dewi; Indah Kurnia Utami; Darmayanti; Syafika Alaydrus; Wawang Anwarudin (Universitas Ahmad Dahlan, 2024)
Purple leaves (Graptophyllum pictum L. Griff) are one plant that is widely used as a medicine. Purple leaves have pharmacological activities that can be used as medicine, including antioxidants, antiinflammatory, antidiabetic, analgesics, immunomodulators, antihemorrhoids, and antibacterial. The objective of this study was to determine the antioxidant properties of ethanol extract from purple leaves as well as its properties as an analgesic and anti-inflammatory against Wistar rats. Antioxidant activity was measured using the DPPH method with quercetin as a comperation in vitro the in vivo study of 25 Wistar rats was divided into 5 groups consisting of 5 animals each, namely normal control, positive control, negative control, treatment group with a dose of 50 mg/kg BW and treatment group with a dose of 100 mg/kg BW. The analgetic activity test was conducted by the writhing test method, while antiinflammatory activity was measured by measuring the percentage of inflammatory volume using a mercury plethysmometer. The data was analyzed using the One-way ANOVA SPSS software program. The results showed that antioxidant activity showed an IC50 value of 72.312 ± 24.406 μg/mL (strong antioxidant). Meanwhile, in the analgetic test, the highest percentage of analgesic effectiveness was found at a dose of 100 mg/kg BW with a value of 129.64% and showed anti-inflammatory activity at a dose of 100 mg/kg BW with a percentage decrease in edem volume of 28.73% at the sixth hour.